Speech, Gait, and Vestibular Function in Cerebellar Ataxia with Neuropathy and Vestibular Areflexia Syndrome - Giulia Di Rauso; Andrea Castellucci; Francesco Cavallieri; Andrea Tozzi; Valentina Fioravanti; Edoardo Monfrini; Annalisa Gessani; Jessica Rossi; Isabella Campanini; Andrea Merlo; Dario Ronchi; Manuela Napoli; et al. (Brain Sciences, 2023)
(1) Background: Cerebellar ataxia with neuropathy and vestibular areflexia syndrome (CANVAS) is characterized by late-onset cerebellar ataxia, bilateral vestibulopathy, and sensory neuronopathy mostly due to biallelic RFC1 expansion. (2) Objectives: The aim of this case series is to describe vestibular, gait, and speech alterations in CANVAS via a systematic approach. (3) Methods: All patients (n = 5) underwent a standardized clinical–instrumental examination, including the perceptual and acoustic analysis of speech, instrumental gait, and balance analysis (posturographic data were acquired using a force plate [Kistler, Winterthur, Switzerland] while 3D gait analysis, inclusive of surface electromyography, was acquired using a motion capture system [SMART DX, BTS Bioengineering, Milan, Italy], a wireless electromyograph [FreeEMG, BTS Bioengineering, Milan, Italy]), and vestibular assessment with video-oculography. (4) Results: Five patients were included in the analysis: three females (patients A, B, C) and two males (patients D and E) with a mean age at evaluation of 62 years (SD ± 15.16, range 36–74). The mean age of symptoms’ onset was 55.6 years (SD ± 15.04, range 30–68), and patients were clinically and instrumentally evaluated with a mean disease duration of 6.4 years (SD ± 0.54, range 6–7). Video-Frenzel examination documented spontaneous downbeat nystagmus enhanced on bilateral gaze in all patients, except for one presenting with slight downbeat nystagmus in the supine position. All patients exhibited different degrees of symmetrically reduced VOR gain for allsix semicircular canals on the video-head impulse test and an unexpectedly normal (“false negative”) VOR suppression, consistent with combined cerebellar dysfunction and bilateral vestibular loss. Posturographic indices were outside their age-matched normative ranges in all patients, while 3D gait analysis highlighted a reduction in ankle dorsiflexion (limited forward rotation of the tibia over the stance foot during the stance phase of gait and fatigue of the dorsiflexor muscles) and variable out-of-phase activity of plantar flexors during the swing phase. Finally, perceptual-acoustic evaluation of speech showed ataxic dysarthria in three patients. Dysdiadochokinesis, rhythm instability, and irregularity were observed in the oral diadochokinesis task. (5) Conclusions: CANVAS is a recently discovered syndrome that is gaining more and more relevance within late-onset ataxias. In this paper, we aimed to contribute to a detailed description of its phenotype.